2008
DOI: 10.1111/j.1745-493x.2008.00053.x
|View full text |Cite
|
Sign up to set email alerts
|

Buyer–supplier Relationships: Derived Value Over Two Decades

Abstract: This paper reviews studies of buyer–supplier relationships published in four prominent U.S.‐based academic journals between 1986 and 2005. Our review revealed that the focus of academic researchers on types of value being extracted from buyer–supplier relationships changed between 1986 and 2005, as did their interest in the buyer mechanisms implemented to create value in these relationships. Although emphasis has changed over time, we found that scholars have primarily investigated four types of value derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
237
2
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(256 citation statements)
references
References 134 publications
(201 reference statements)
8
237
2
9
Order By: Relevance
“…The degree to which participants strategically collaborate with its partners and the extent of collaborative management of the intra and inter-organizational processes will depend on the collaborative or coercive use of power by dominant players. A comprehensive review of buyer-supplier relationships from 1986 to 2005 by Terpend et al (2008) found that research focused initially on operational improvements and later the focus shifted to financial performance of the participating firms. The four main improvements that buyers and suppliers typically seek from their collaborative relationships are: operational improvements; integration-based improvements; supplier capability-based improvements and financial performance.…”
Section: Types Of Power In Supply Chainsmentioning
confidence: 99%
“…The degree to which participants strategically collaborate with its partners and the extent of collaborative management of the intra and inter-organizational processes will depend on the collaborative or coercive use of power by dominant players. A comprehensive review of buyer-supplier relationships from 1986 to 2005 by Terpend et al (2008) found that research focused initially on operational improvements and later the focus shifted to financial performance of the participating firms. The four main improvements that buyers and suppliers typically seek from their collaborative relationships are: operational improvements; integration-based improvements; supplier capability-based improvements and financial performance.…”
Section: Types Of Power In Supply Chainsmentioning
confidence: 99%
“…Similarly, several studies have been published explaining the empirical outcomes of supplier development approaches towards improved buyer-supplier relationships through suppliers' integration, collaborative product development and planning, and information system etc. [57][58][59][60][61][62] and [63]. Further, the results of supplier development approaches clearly demonstrate not only a positive impact on firm's financial performance but also enhancing the operational competencies [61,64] and [65].…”
Section: Supplier Development To Buyer-supplier Relationship Developmentmentioning
confidence: 99%
“…The former refer to improved cooperation and reduction of risk and opportunism. The latter refer to demands by buying firms on their suppliers regarding capability-based goals such as achieving new product development (Terpend et al, 2008). Both elements are taken into consideration in the literature on supplier involvement in new product development, which I will try to extend.…”
Section: (B) Supplier Involvement In New Product Developmentmentioning
confidence: 99%
“…Scholars studying buyer-supplier relationships have primarily investigated four types of value derived from buyer-supplier relationships: operational performance improvements, integration-based improvements, supplier capability-based improvements and financial performance outcomes, as pointed out in a review by Terpend et al (2008). Dealing with the effects of supplier-buyer relationships on innovation, in this thesis I am focusing on integrationbased improvements, and supplier capability-based improvements.…”
Section: (B) Supplier Involvement In New Product Developmentmentioning
confidence: 99%